Are You a Soft Target for Cyber Attack? Drivers of Susceptibility to Social Engineering-Based Cyber Attack (SECA): A Case Study of Mobile Messaging Application - Nuri Wulandari; Mohammad Syauqi Adnan; Chastio Bayu Wicaksono (Human Behavior and Emerging Technologies)
A rise in working and studying from home, activities which depend on the Internet, and the exchange of data coupled with a lack of understanding about security for interacting in cyberspace have made cybersecurity one of the most pressing concerns today. One form, in particular, is a social engineering-based cyber attack. Unfortunately, not much research has been conducted on the susceptibility factors that cause this to happen. This study attempts to understand what factors make a person susceptible to cyber attacks that can be seen from three perspectives: habitual perspective, perception perspective, and social and motivation perspective. The objective of the research is to identify specific characteristics and drivers regarding the social engineering-based cyber attack (SECA) susceptibility of a consumer exposed to social media messaging applications. A quantitative survey was employed to test a total of 114 respondents in Indonesia who are categorized as active Internet users. The study found variables within two of the three perspectives that positively contributed to a consumer’s susceptibility to cyberattack. These factors will provide valuable insight into prevention and knowledge of related risks of cyberattacks based on social engineering in the future.